Living as Textual Animals: Curriculum, Sustainability and the Inherency of Language - Howard, Patrick (Journal of the Canadian Association for Curriculum Studies, 2011)
<!--[if gte mso 9]> Normal.dotm 0 0 1 207 1182 York University 9 2 1451 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> The ecosystems that sustain us are sending warning signals we ignore at our peril. Environmental and economic indicators tell us how we live in our respective places must change radically. Education in general and curriculum developers specifically, struggle to find an appropriate response to an impending crisis. Literacy learning focuses on the spoken and written word as well as representation that contribute vitally to how individuals understand maintain and transform their worldview. The language arts classroom is potentially a powerful site for challenging taken for granted cultural assumptions. A research project undertaken with middle school students was designed to allow the students to address questions that increase awareness of how we live in our places. The project provided students the space to record connections, observations, descriptions and evidence of ecological relationships that emerge out of daily living. By attending to felt sense through an embodied approach to writing and response, students developed a deeper sensibility for the existence of their ecological selves. Students were able to sensitively address inner connectivities of body, mind and emotions to awaken and develop a deeper connection with the living landscapes in which they dwell demonstrating the integral role the literacy classroom will have in efforts to re-orient education to teach for the values of sustainability. <!--EndFragment-->